2010
DOI: 10.1159/000281404
|View full text |Cite
|
Sign up to set email alerts
|

Hook Effect: A Pitfall Leading to Misdiagnosis of Hypoaldosteronism in an Infant with Pseudohypoaldosteronism

Abstract: We report herein the case of a premature infant who presented with failure to thrive, hyponatremia, hyperkalemia and metabolic acidosis. Initial serum hormone profiling suggested isolated hypoaldosteronism (aldosterone: 0.01 pg/ml, normal range: 50–900 pg/ml). A gas chromatography-mass spectrometry spot urinary steroid profile showed grossly elevated levels of 18-hydroxy-tetrahydro-11-dehydrocorticosterone (18-hydroxy-THA: 5,893 µg/l; normal upper limit 36 µg/l) and tetrahydroaldosterone (TH-Aldo: 5,749 µg/l; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Due to the hook effect caused by very high aldosterone levels in Patient 8, the aldosterone level was found to be very low and caused a misdiagnosis. The first eight-month progress of Patient 8, who is 8 years old now, was also reported by Akin et al (7). The second point that may cause an error is the possibility of measuring higher aldosterone levels in severe sepsis cases and CAH cases due to the interference of other hormones and precursors.…”
Section: Discussionsupporting
confidence: 69%
“…Due to the hook effect caused by very high aldosterone levels in Patient 8, the aldosterone level was found to be very low and caused a misdiagnosis. The first eight-month progress of Patient 8, who is 8 years old now, was also reported by Akin et al (7). The second point that may cause an error is the possibility of measuring higher aldosterone levels in severe sepsis cases and CAH cases due to the interference of other hormones and precursors.…”
Section: Discussionsupporting
confidence: 69%
“…This phenomenon was first described by Miles (16) with a two-site immunoradiometric assay (IRMA) for ferritin. Hook effect in measurements of GH (17), PRL (18), TSH (19), FSH, LH (20), human chorionic gonadotropin (21) and aldosterone (22) have been reported previously. To our knowledge, this is the first case where a hook effect is reported for testosterone.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, accurate and reliable measurements of PRA and plasma aldosterone are notoriously difficult . In PHA, extremely high aldosterone levels can erroneously be measured as low (hook effect), leading to the misdiagnosis of IHA . Furthermore, compensated CAH patients can have high aldosterone levels that can mimic PHA .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In PHA, extremely high aldosterone levels can erroneously be measured as low (hook effect), leading to the misdiagnosis of IHA. 19 Furthermore, compensated CAH patients can have high aldosterone levels that can mimic PHA. 16 Three of the IHA patients in this study whose initial endocrinological evaluation showed hyperreninaemic hypoaldosteronism had been successfully treated with fludrocortisone.…”
Section: Discussionmentioning
confidence: 99%